Efficient Synthesis of 7,8-Dihydro-6H-benzo[c]chromen-6-one Derivatives by Base-Mediated Chemoselective Annulation of Alkylidene Malononitriles with α,β-Unsaturated Coumarins - Alizadeh, Abdolali; Farajpour, Behnaz; Khanpour, Mojtaba (Synlett, 2021)
An efficient and chemoselective synthesis of biologically valuable 7,8-dihydro-6H-benzo[c]chromen-6-ones is described. In this method, neither a metal catalyst nor expensive starting materials are needed, and the products can be purified by simple filtration and washing with EtOH. Readily available starting materials, green and mild conditions, synthetically useful yields, and operational simplicity are some highlighted advantages of this unprecedented transformation.
Keywords: alkylidenemalononitriles; coumarins; benzochromenones; 6π-electrocyclic ring closure; hydride shift